The Dynamics and Factors Influencing The Land Use/Land Cover Change in Ciparay District, Bandung Regency - Ryan Prima Chandra; Lia Warlina (Universitas Diponegoro, Indonesia, 2023)
Population growth in Ciparay District, as in several areas in West Java Province, has been increasing, especially in the last ten years, leading to an increase in housing needs and converting rice fields to residential land. This study aims to identify the spatial conversion dynamic of rice fields and analyze the factors that influence the conversion of rice fields in Ciparay District, Bandung Regency. The method used in this research is a quantitative descriptive method with map overlay analysis techniques and multiple linear regression analysis. This study found that the characteristics of land conversion in Ciparay District are divided into four land use/ land cover changes: rice field to residential land, rice field to dryland farming, rice field to vacant land, and dryland agricultural to settlement. The most significant change in land use/ land cover is in the change of rice fields to residential areas, which is 336.09 hectares. The factor that had the most influence on the land conversion of rice fields was the accessibility ratio.